SEM Analysis Of Human Rights Youth Advocacy Model - KM Ashifa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to pressure from different social movements, the last quarter of the 20th century witnessed an rising awareness of position and importance of human rights. People are aware of their citizens' rights and responsibilities. Indeed, today's consumerist culture is faced with crimes that threaten human rights. Youth engagement in the process of sharing a culture of human rights would create a dignified and equal society. The present investigation aims to examine the activities of youth to support human rights advocacy and to establish an institutional model for initiatives to promote human rights. The research used “structural equation modeling (SEM)” as a statistical method to test the relations between observed and latent variables to improve young people 's role in action on human rights. The position of advocacy can be defined on the basis of empowerment, protection and restoration and, anti-oppression.